Storm front - Sandford, John, 1944 February 23- (New York : G. P. Putnam's Sons, 2013)
Approached by an Israeli police officer who is tailing a man in possession of a stolen religious relic, Virgil Flowers learns that the artifact reveals startling details about the biblical King Solomon and that dangerous rivals are killing everyone who would protect it.
Keywords: Flowers, Virgil (Fictitious character) -- Fiction; Government investigators -- Minnesota -- Fiction; Minnesota -- Fiction; Detective and mystery stories; Mystery fiction